STRATEGI PENERJEMAHAN TAMYÄªZ DALAM BUKU AT-TIBYÄN FÄª ÄDÄBI CHAMALATIL-QURâÄN KARYA IMAM AN-NAWAWI - Abdul Malik, Ahmad Falahudin (Jurnal CMES, 2017)
This research aims to describe the types of tamyÄ«z (accusative of specification) translation and strategies of translation applied by translator to translate tamyÄ«z on Imam Nawawiâs At-TibyÄn FÄ« ÄdÄbi Chamalatil-QurâÄn (TACQ). The method used in this research is descriptive qualitative. Conducted by observation and marking technique, the collecting data was done by non-interactive method that is identifying and classifying the types of tamyÄ«z found in source language, and matching them with target language translation. The analyzing data uses 3 steps i.e reducing data, presenting, and concluding. The results of this research reveal there are 3 types of tamyÄ«z that are tamyÄ«z asmÄul aâdÄd, tamyÄ«z muchawwal âan mubtadaâ and tamyÄ«z muchawwal âan mafâÅ«l. These types of tamyÄ«z was translated into target language by set of constructs noun phrase, verb phrase, and counted noun phrase. Second, the translator applied 8 strategies of translation to translate tamyÄ«z in TACQ. Among these strategies, the semantic strategy was the most used strategy than others. It was used in 64,29%, whereas structural strategy was used in 35,71%. Itâs clear to conclude that the translator favors meaning aspect to translate message clearly and effectively in target language.